2016
DOI: 10.1016/j.mmcr.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Current strategies against invasive fungal infections in patients with aplastic anemia, strong power and weak weapon, a case report and review of literature

Abstract: We report an 18 year old boy with Aplastic anemia complicated by serious fungal rhinosinusitis. Despite prompt treatment and early repeated surgical debridements, he died after about more than 6 weeks of hard challenges with fungal infections. Current strategies against invasive fungal infections (IFIs) in patients with Aplastic anemia may be inadequate for the management of serious complications. Antifungal prophylaxis is highly recommended in pre-transplant period for severe form of Aplastic anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous research has reported that iron deficiency causes calcium overload and increased intracellular accumulation of reactive oxygen species (ROS), thereby leading to disturbed ion homeostasis and finally suppressing fungal growth [ 24 ]. However, aplastic anemia patients were proven to have an increased prevalence of fungal infections [ 25 ]. However, the present study result was contradictory to this observation since 53.5% of our study population had a history of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that iron deficiency causes calcium overload and increased intracellular accumulation of reactive oxygen species (ROS), thereby leading to disturbed ion homeostasis and finally suppressing fungal growth [ 24 ]. However, aplastic anemia patients were proven to have an increased prevalence of fungal infections [ 25 ]. However, the present study result was contradictory to this observation since 53.5% of our study population had a history of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the necrotic tissues that preclude the sufficient delivery and penetration of the antifungals into the affected area may have led to further invasion to the periorbital and neurovasculature areas resulting in death. Antifungal prophylaxis is recommended for the prevention of invasive fungal infection in pre-transplant period; however, it remains uncertain for other high-risk groups [23].…”
Section: Discussionmentioning
confidence: 99%